Comparison of RPL14 expression levels between normal and tumour cells of juma nasopharyngeal epithelium - Nur Atiqah, Azman (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Nasopharyngeal carcinoma (NPC) is predominant cancer in Southern China and Southeast Asia which affect Cantonese inheritance. Previous research showed that ribosomal preteins (RPs) gene expression in nasopharyngeal carcinoma (NPC) are differ frim normal human nasopharyngeal epithelium cells with most RPs that are being down-regulated. Recent studies showed that disturbance of RPs might induce tumorigenesis. However, there is a lack of study done regarding RPL14 specific investigation on NPC. Therefore, this study is proposed to extract Ribosomal Protein L14 gene (RPL14) to compare the differences on expression level in human nasopharyngeal cell lines (normal and carcinoma) by using a standard protocol, RNA was extracted by Trizol as starting material in this project and amplified using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) with the aid of software Image Quant TL. This study revealed the PCR product wiht a length of 760 bp in RPL14. There is significant difference of RPL14 expression levels in NPC.